2015
DOI: 10.1159/000377628
|View full text |Cite
|
Sign up to set email alerts
|

Has Previous Abuse of Flunitrazepam Been Replaced by Clonazepam?

Abstract: Background and Aims: For many years, flunitrazepam was the benzodiazepine of choice among users of illegal drugs. The aim of this study was to investigate to which extent clonazepam use has increased in this population, and whether this was related to increased prescription or because of illegal availability. Methods: We used data from three sources to study the changes in the use of clonazepam: (1) Presence and concentrations of clonazepam and flunitrazepam in blood samples collected from Norwegian drugged dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…A study found that 12% of clonazepam redemptions in Norway were reimbursed [ 21 ], indicating frequent ‘off-label’ use. For the last 10 years, a significant increase in the illegal use of clonazepam has been seen in Norway [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study found that 12% of clonazepam redemptions in Norway were reimbursed [ 21 ], indicating frequent ‘off-label’ use. For the last 10 years, a significant increase in the illegal use of clonazepam has been seen in Norway [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another key finding is the continuing emergence of clonazepam and decline of flunitrazepam as a benzodiazepine of misuse in heroin users. Clonazepam was found to be the most common benzodiazepine, although this is largely due to the fact that a large proportion of the study data originated from Oslo, where clonazepam was found to be the most commonly used benzodiazepine [27]. In addition, the use of flunitrazepam was rarely reported by patients in this study.…”
Section: Choice Of Benzodiazepinesmentioning
confidence: 69%
“…Out of the 6307 patients who initiated benzodiazepine or Z‐drug treatment, 3.5% used clonazepam or alprazolam, both of which are among the most common drugs of abuse worldwide . Alprazolam has long been known for causing more severe physical dependence than other benzodiazepines, due to its high potency .…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 6307 patients who initiated benzodiazepine or Z-drug treatment, 3.5% used clonazepam or alprazolam, both of which are among the most common drugs of abuse worldwide. [31][32][33] Alprazolam has long been known for causing more severe physical dependence than other benzodiazepines, due to its high potency. 34 Similarly, warnings about the highly addictive properties of clonazepam have emerged in recent years, 35,36 indicating that the high rates of longterm use of these drugs may be due to patients becoming dependent.…”
Section: Discussionmentioning
confidence: 99%